Study on Incidence of Major Insect Pests and Parasitism in Sesame Crop: Impact of insect pests and biological control on sesame crop productivity (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Insect pests create problems to farmers by damaging crop and decreasing productivity. The sesame yield is greatly affected by the attack of insect pests. In our country, farmers are using various kinds of synthetic chemical pesticides for plant protection from a long period of time. These pesticides are degrading the quality of cereals as well as environment. To overcome this problem, it is important to replace these pesticides by biological control to maintain the quality of food environment. In the present study, a field experiment was carried out on incidence of insect pests and parasitism in sesame crop. Larval parasitoids Bracon sp., on Leaf Webbercapsule borer, Antigastra catalaunalis, and Apanteles sp. on bihar hairy caterpillar, Spilosoma oblqua, a polyphagous insect pest were found during field survey and the rearing of these insect pests in Entomology Research Laboratory, Agra College Agra.